The risk of Angiotensin Converting Enzyme Inhibitor (ACEI) and Calcium Channel Blocker (CCB) used on Obstructive Sleep Apnea (OSA) incidence in hypertension patients - Fibe Yulinda Cesa; Martanty Aditya; Rehmadanta Sitepu; Dion Notario (Jurnal Ilmiah Farmasi, 2022)
AbstractBackground: The administration of angiotensin-converting enzyme inhibitor (ACEI) and calcium channel blocker (CCB) therapy is known to have a side effect of a dry cough that would trigger OSA. Further research is needed to compare the effect of these two drugs on the side effects of OSA, which could trigger high-risk patient conditions.       Objective: To determine the risk of using ACE and CCB on the incidence of OSA using a case-control study method at Dau Primary Health Center.Methods: Demographic data were collected on 207 respondents aged 40-60 years by collecting Data Collection Sheets and Berlin questionnaires to determine the risk of OSA in respondents. Then, statistical analysis was carried out by determining the odds ratio (OR).Results: The results showed that one of the factors BMI (obese BMI; OR=1.33; 95% CI=0.11-15.70) induces OSA with the highest OR value compared to other factors.Conclusion: Obese patient has a 1.33 times greater risk of OSA with ACEI and CCB therapy than non-obese. It is necessary to conduct further research with a larger sample size related to OSA’s assessment associated with this therapy to improve patients’ quality of life.Keywords: Obstructive sleep apnea, ACE inhibitors, calcium channel blockers, hypertension IntisariLatar belakang: Obtructive Sleep Apnea (OSA) yang terjadi pada pasien hipertensi dapat disebabkan karena efek samping dari penggunaan antihipertensi angiotensin converting enzyme inhibitor (ACEI) dan calcium channel blocker (CCB), namun analisis hubungan keduanya belum diketahui dengan pasti.Tujuan: Penelitian ini bertujuan untuk mengetahui risiko penggunaan ACE dan CCB terhadap kejadian OSA dengan metode case control study di Puskesmas Dau.Metode: Pengambilan data demografi pada 207 responden usia 40-60 tahun dilakukan dengan mengumpulkan Lembar Pengumpul Data (LPD) dan kuesioner Berlin untuk mengetahui risiko OSA pada responden kemudian dilakukan analisis statistik dengan penentuan odds ratio (OR).Hasil: Hasil penelitian menunjukkan bahwa pasien yang menjalani pengobatan dengan antihipertensi ACEI dan obesitas memiliki risiko lebih besar mengalami OSA (OR=1,33; CI 95%=0,11-15,70)  yaitu 1,33 kali dibandingkan pada pasien yang tidak obesitas.Kesimpulan: Obesitas menjadi factor risiko terhadap kejadian OSA pada pasien hipertensi yang mendapatkan antihipertensi golongan ACEI dan CCB.Kata kunci: Obstructive sleep apnea, ACE inhibitor, calcium channel blocker, hipertensi